KETERLIBATAN ORANG TUA DALAM PENDIDIKAN ANAK USIA DINI PADA TK AL-IKHLAS TANJUNG SARI NATAR KABUPATEN LAMPUNG SELATAN - Puspitasari, Tuti; Uminar, Ajeng Winda; Anggraeni, Wardah (STIT AL MULTAZAM, 2021)
This study aims to explain how efforts are being made to facilitate parental involvement in early childhood education at Al-Ikhlas Kindergarten Tanjung Sari Natar, South Lampung Regency. Data collection methods used in this research include interviews, observation, and documentation with descriptive data analysis. The data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results showed that: first, the factors that influence the involvement of parents at Al-Ikhlas Tanjung Sari Natar Kindergarten in South Lampung Regency in educating children include social status factors, family form factors, family development stage factors, and role model factors; second, the efforts that have been made to facilitate parental involvement in early childhood education at Al-Ikhlas Tanjung Sari Natar Kindergarten, South Lampung Regency, namely: parenting education, information on education, development, and child health, learning at home, children's performances , recreation, collaboration with the community (the highlight of the theme), home visits by teachers, and participation in school activities.